Answer:10.25
Step-by-step explanation:
Answer:
20
Steps-by-step explanation:
sorry mistake
Answer:
-1
Step-by-step explanation:
First, we need to work out the left-hand side.
- find g(2) → g(2) = 2 - 1 which is 1
- next, find f(1) → f(1) = 1³ which is 1
Now, we can work out the right hand side.
- find f(-1) → f(-1) = -1³ which is -1
- then, find g(-1) → g(-1) = -1 - 1 = -2
Finally we can work out the full sum: 1 + -2 = -1.
Hope this helps!
Answer:
20,300
Step-by-step explanation:
The answer is A the line isn't sloping they are on the same y axis